Utilização de API para geolocalização em tempo real de encomendas pedidas por meio de um aplicativo mobile multiplataforma - Oliveira, Douglas Wender Lopes de (2022)
Due to the pandemic of the new coronavirus, e-commerce has intensified more and more. This phenomenon can be observed mainly in small and medium businesses. As a result, due to practicality and quality, we follow a demand increase for delivery services. Currently, Correios is one of the most extensive Brazilian delivery services. However, its high cost and delivery time shipping are not very attractive. For this reason, the search for alternative delivery methods has grown increasingly on platforms such as Facebook and Whatsapp. Aiming at the negative points of traditional shipping methods, searching for "delivery hitchhikers"between nearby cities or even large urban centers has become a popular alternative method. With this in mind, the present work proposes a multi-platform application using the Framework Flutter jointly with the Google geolocation API. This API includes maps and routes for publishing, selecting, sending, and tracking orders, thus connecting drivers, senders, and recipients; to quickly and securely complete shipments and deliveries.